EVALUATION OF THE THERMAL PERFORMANCE OF METAL ROOFING UNDER TROPICAL CLIMATIC CONDITIONS - Harimi, Mohamed; Harimi, Djamila; Kurian, V.J.; Bolong, N. (CREAM, CIDB Malaysia, 2006)
The assessment of the thermal performance was carried out on a low cost house mainly built from waste oil palm shell (OPS-Concrete) with galvanized steel-roof. It was noticed that reasonable thermal comfort took place during the night for the roof without ceiling and without insulation, and during the day at a peak temperature of a highly ventilated attic area. For such situation, it was recommended to install insulating horizontal plated surface under the roof, which should be turned into a vertical position during the night. Other alternatives may be creating small adjustable openings around building envelope just under the ceiling or making an open roof-ceiling system. This technique will reduce the heat flux from insulated ceiling by the flow of the cooling air at night, but the impact of surrounding microclimate on human thermal comfort should be considered. The mathematical model used to predict the attic temperature for a lightweight roof system was obtained by correlation, which can be used for a quick inspection. Insulation materials of 50 mm fibreglass and foil-aluminium were used with sealed attic, and found the ceiling temperature reduced by about 3 oC and 2 oC respectively. For the case of fibreglass of thickness beyond 50 mm, the reduction of ceiling temperature was recorded less than ½ oC, really not attractive. Keywords: thermal performance, metal roofing, attic temperature, sealed attic, ventilated attic, insulation